Integrated Reporting Quality: Institutional Antecedents And Consequence On Firm Performance - Wong, Kar Shun (2022)
Integrated reporting (IR) is a novel concept of corporate reporting which has drawn immense interest among academics, practitioners, and regulators over the last decade. Primarily using institutional theory, this study endeavours to examine a set of institutional isomorphic influences towards IR quality and the role of board independence in moderating such influences.